What do time-use patterns tell us about the validity of self-reported health? - Marco Faytong-Haro; Alexis R. Santos-Lozada (Elsevier, 2021)
Objective: This short communication investigates the usefulness of time-use measures to validate subjective health measures such as self-reported health (SRH). It does this by examining time-use patterns and SRH among middle-age adults in the United States distinguished by race/ethnicity and with additional attention to differences in responses based on language of interview for Hispanics. Methods: Data for this study come from the 2013-2016 American Time Use Survey. We calculated average time-use for personal care; housework; paid work; leisure; volunteering/travel; caregiving; and education for every racial/ethnic group differentiating by SRH for 27,063 adults aged 25-64 years. A series of ANOVAs were computed to assess differences in time-use by SRH. Results: Non-Hispanic whites and non-Hispanic Blacks who reported poor/fair SRH spent more time in personal care and leisure, and less time in paid work, volunteering/travel, caregiving and education, in comparison to those who reported Excellent/Very Good/Good SRH. Among Hispanics, differences by SRH were found for personal care, paid work, leisure and volunteering/travel. Hispanics who answered in English displayed partially similar patterns in SRH found for non-Hispanic whites and Blacks. Hispanics who answered in Spanish demonstrated differences in SRH in the areas of paid work, leisure and education, diverging from the other groups. Conclusions: Time-use differences by health status are consistent between non-Hispanic whites, non-Hispanic blacks, but not so for Hispanics. To some extent, Hispanics who answered in English have more comparable patterns to non-Hispanic whites and non-Hispanic Blacks than Spanish respondents. Caution should be exercised when self-reported health measures are used to compare diverse samples collected with surveys that are administered in different languages.